Development of Mobile Application for Accounting Subject - Hakim Azammullah, Muhammad Akmal; Ahmad Zaki, Nadia Akma; Manaf, Abdi (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2024)
This study aims to develop a mobile application called "On-Lejar" to assist Form 4 students in learning the Ledger (Lejar) topic in accounting. The application addresses the limited availability of online study aids for accounting, which has led to difficulties in mastering the Ledger topic. Traditional teaching methods, which often rely solely on direct instruction from teachers, can hinder student engagement and interest in accounting. By incorporating multimedia and information technology elements, the On-Lejar application seeks to enhance the learning experience for both students and educators. The Agile Model guided the application’s development, and functionality tests conducted with 10 respondents through questionnaires indicated high satisfaction with the app's overall performance, encouraging further learning and use. Additionally, the study highlights the role of Open Distance Learning (ODL) in ensuring continuity in education, especially during the COVID-19 pandemic. Educational applications, including the On-Lejar app, have become vital in facilitating home teaching and learning activities, promoting student engagement and flexible access to resources. Future recommendations include continuous innovation in educational applications to maintain user interest. Overall, the research underscores that engaging learning experiences can be achieved beyond the traditional classroom setting through well-developed mobile applications.